2022
DOI: 10.3390/cells11233883
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induced by Toll-like Receptor Ligands Regulates Antigen Extraction and Presentation by B Cells

Abstract: The engagement of B cells with surface-tethered antigens triggers the formation of an immune synapse (IS), where the local secretion of lysosomes can facilitate antigen uptake. Lysosomes intersect with other intracellular processes, such as Toll-like Receptor (TLR) signaling and autophagy coordinating immune responses. However, the crosstalk between these processes and antigen presentation remains unclear. Here, we show that TLR stimulation induces autophagy in B cells and decreases their capacity to extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In line with this, another study reported the accumulation of LC3 with the internalized antigen (Runsala et al, 2023), together indicating that autophagy-linked protein machinery is activated in response to B cell IS formation and involved in targeting the internalized antigen for further processing. Interestingly, tolllike receptor ligands, such as lipopolysaccharide (LPS), restrict lysosome repositioning to the IS of B cells by triggering autophagy-dependent degradation of GEF-H1, a Rho GTP exchange factor required for stable lysosome recruitment at the synaptic membrane (Lagos et al, 2022). The BCR activation state can regulate the autophagic signature in a manner dependent on the cell stage and the local microenvironment: it was recently proposed that a switch from mTORC1-driven canonical to noncanonical autophagy occurs in the germinal center (GC) B cells upon B cell activation, proposing that the B cell stage and location in situ may influence the responses to antigen exposure via alternating the autophagy route (Martinez-Martin et al, 2017;Raza and Clarke, 2021).…”
Section: Hämälistö Et Almentioning
confidence: 99%
“…In line with this, another study reported the accumulation of LC3 with the internalized antigen (Runsala et al, 2023), together indicating that autophagy-linked protein machinery is activated in response to B cell IS formation and involved in targeting the internalized antigen for further processing. Interestingly, tolllike receptor ligands, such as lipopolysaccharide (LPS), restrict lysosome repositioning to the IS of B cells by triggering autophagy-dependent degradation of GEF-H1, a Rho GTP exchange factor required for stable lysosome recruitment at the synaptic membrane (Lagos et al, 2022). The BCR activation state can regulate the autophagic signature in a manner dependent on the cell stage and the local microenvironment: it was recently proposed that a switch from mTORC1-driven canonical to noncanonical autophagy occurs in the germinal center (GC) B cells upon B cell activation, proposing that the B cell stage and location in situ may influence the responses to antigen exposure via alternating the autophagy route (Martinez-Martin et al, 2017;Raza and Clarke, 2021).…”
Section: Hämälistö Et Almentioning
confidence: 99%